Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1097/01.ccm.0000275269.77467.df
|View full text |Cite
|
Sign up to set email alerts
|

High tidal volume is associated with the development of acute lung injury after severe brain injury: An international observational study*

Abstract: In addition to a lower Pao2/Fio2, the use of high tidal volume and high respiratory rate are independent predictors of acute lung injury in patients with severe brain injury. In this patient population, alternative ventilator strategies should be considered to protect the lung and guarantee a tight CO2 control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
158
1
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(178 citation statements)
references
References 35 publications
8
158
1
8
Order By: Relevance
“…It has been shown that use of high tidal volumes (9-11 ml/kg) stimulates inflammatory response and lung injury induced by the ventilator. 10,25,[31][32] Even neurocritical patient's ventilation in prone possition results in improved brain tissue oxygenation in severe hypoxemia with minimal effect on Intracranial pressure (ICP) and Cerebral Perfusion Pressure (CPP).…”
Section: Prevention Of Collapse /Atelectasis In Decline Areasmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that use of high tidal volumes (9-11 ml/kg) stimulates inflammatory response and lung injury induced by the ventilator. 10,25,[31][32] Even neurocritical patient's ventilation in prone possition results in improved brain tissue oxygenation in severe hypoxemia with minimal effect on Intracranial pressure (ICP) and Cerebral Perfusion Pressure (CPP).…”
Section: Prevention Of Collapse /Atelectasis In Decline Areasmentioning
confidence: 99%
“…Its severity is related to the magnitude of the brain injury and it is associated with high morbidity rates and up to 7% mortality. 8,10,25 NPE may be triggered by different brain conditions, including seizures, stroke and traumatic brain injury ( Figure 3). NPE is most common in seizures during the post-critical period, affecting to up to one third of patients in status epilepticus.…”
Section: Neurogenic Pulmonary Edema (Npe)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cada vez hay más evidencia que la ventilación con alto volumen corriente también puede producir daño en pacientes con pulmones sanos 48,51 . En un estudio prospectivo observacional en 86 pacientes con trauma cerebral grave, Mascia et al, mostraron que 22% de ellos desarrolló SDRA durante las primeras 72 h de ventilación, siendo el uso de un Vt elevado (> 11 ml/kg IBW) un predictor independiente para el desarrollo de esta complicación 50 . En forma más reciente, Determann et al, demostraron que un Vt de 10 ml/kg IBW aumentó el desarrollo de SDRA de 2,6% a 13,5% (p < 0,001) en relación al uso de Vt 6 ml/kg IBW en 150 pacientes sin daño pulmonar 51 .…”
Section: Manejo Ventilatorio Del Potencial Donante Cadáverunclassified
“…Parece que hay evidencia que indicaría utilizar ventilación protectora, con bajos volúmenes tidales. Los pacientes ventilados con volúmenes mayores tienen una frecuencia de lesión pulmonar aguda mayor, y es un factor independiente 10 . Se puede asociar a otros factores que también elevan la incidencia de lesión pulmonar, algunos intracraneales y otros extracraneales: fármacos vasoactivos, actividad inflamatoria, actividad simpática, etc.…”
Section: Medidas Generalesunclassified